SHARE LIQUIDITY ANALYSIS BEFORE AND AFTER STOCK SPLIT AT INDONESIA IN YEAR 2008 - Magdalena, Maria (Accounting, 2010)
Liquidity is a measure of the number of shares of stock transactions on the capital market within a certain period. The higher frequency of transactions, the higher liquidity of shares, this means the stock is increasingly in demand by investors and it will level the relevant share price. A liquid is said shares when the stock is easy to be exchanged or used as money. Illiquid shares that would cause a loss of opportunity to profit. Keyword : Liquidity, Transaction, Exchanged